HOW ASEAN PERCEIVE NATURAL DISASTER AS PART OF SECURITY COMMUNITY AGENDA? - Alifia Putri Rahmadewi; Arfin Sudirman (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2021)
As a disaster-prone area, ASEAN had a set of disaster management mechanisms. In 2011 ASEAN established an institution that focuses on regional disaster management, namely the AHA Centre. However, the AHA Center did not show its significant role in some disasters. This article aimed to determine the obstacles faced by the AHA Center in 4 phases of international disaster management, namely mitigation, preparedness, response, and recovery, and to use the concept of the security community to analyze ASEAN norms, institutions, and collective identity and relation to disaster management through the AHA Centre. The method used is a qualitative research method. The data collection technique collaborated several techniques derived from interviews with Indonesia’s Ministry of Foreign Affairs, the AHA Center, and BNPB RI, document-based research, and internet-based research. This research showed how the AHA Center had played a role in the four phases of disaster management. However, there were still shortcomings such as its limited role, lack of resource management, and mechanisms that only focused on government-to-government. In addition, this shortcoming can also be found stemming from the collective identity of ASEAN, which is applied in its regional disaster management. Thus, this study suggested that the ASEAN policymakers increase the role of the AHA Center in regional disaster management, improve mechanisms and resource management, and establish cross-pillar mechanisms of the ASEAN community.